TYPOLOGY OF IMAGES OF THE FUTURE IN THE CONTEXT OF GILBERT DURAND’S IMAGINAL STRUCTURALISM - Novikova, Viktoria (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
In contemporary socio-philosophical discourse, the problem of understanding the future is increasingly associated with the analysis of images of the future as symbolic constructions formed within collective imagination. These images reflect cultural archetypes, social expectations, and value orientations of society; therefore, their systematization and typologization become an important research task. The aim and tasks. The aim of the article is to develop a typology of images of the future based on the principles of Gilbert Durand’s imaginal structuralism. To achieve this aim, the study analyzes the role of imagination in the formation of images of the future, examines the theoretical foundations of the concept of the imaginary in Durand’s works, identifies the symbolic structures underlying the formation of images of the future, and carries out their typologization according to the regimes and structures of imagination. Research methods. The methodological basis of the study is Gilbert Durand’s concept of imaginal structuralism, within which imagination is understood as a system of archetypal symbolic structures. The research employs structural-symbolic analysis and the comparative-typological method. Research results. The article substantiates the possibility of typologizing images of the future according to the structures of imagination described in Durand’s theory. Three main types of images of the future are identified: progressive-heroic, regressive-harmonic, and synthetic-cyclical. Each of these types reflects a specific symbolic model of interpreting historical time and sociocultural development. Discussion. The proposed approach correlates with other studies of images of the future in social philosophy and futures studies. Unlike approaches that mainly analyze social scenarios or the functions of images of the future, the method of imaginal structuralism makes it possible to investigate the archetypal symbolic structure of images of the future and the specific features of their formation within imagination. Conclusions. As a result of the study, a typology of images of the future has been developed and three main types have been identified: progressive-heroic, regressive-harmonic, and synthetic-cyclical. The proposed typology makes it possible to systematize diverse sociocultural representations of the future and to reveal the archetypal symbolic schemes through which different models of the future are formed